Opportunities and Challenges of Sukuk Development in the Digital Era: Millennial Generation Perspectives In Indonesia - Fitriana Nur Rohmah; M. Fauzi; Moh. Alfiyan Lu'lu Firdaus (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2023)
Indonesia, as the nation with the highest Muslim population globally, has the potential to benefit from a demographic dividend. Out of the total population of 270 million in Indonesia, generation Z accounts for 27.9%, and millennials make up 25.87%. This means that over 50% of Indonesia's population is in a highly productive age group, making the millennial generation a promising investment group with significant potential in the retail Islamic capital market. Sukuk, an Islamic capital market product, is now being created in Indonesia. This article explores the potential advantages and obstacles associated with implementing sukuk in the digital age, as perceived by the millennial generation. This study employs a qualitative approach through a comprehensive review of relevant literature, focusing on primary sources such as books and journals that specifically address the prospects and obstacles associated with sukuk development. The study's findings indicate a consistent annual increase in the proportion of sukuk, encompassing both corporate and retail sukuk. The potential of sukuk development lies in its ability to serve as an investment instrument that offers chances for both Sharia-compliant and non-sharia-compliant investors. Sukuk's progress intertwines with the millennial generation's principles, making it a robust and adaptive financial instrument that matches social ambitions. Millennials are crucial in shaping Indonesia's economic success by considering Sukuk a significant catalyst.